Process evaluation of a peer-led antenatal breastfeeding class for fathers: perceptions of facilitators and participants - Kuliukas, Lesley; Hauck, Yvonne; Jorgensen, A.; Kneebone, K.; Burns, Sharyn; Maycock, B.; Scott, Jane (BioMed Central Ltd, 2019)
Background: The Parent Infant Feeding Initiative (PIFI) was a factorial, randomised controlled trial that aimed to prolong exclusive breastfeeding by targeting expecting fathers. One of the intervention strategies evaluated was a father-focused breastfeeding class facilitated by a male peer facilitator. The aim of this mixed-methods descriptive study was to 1) evaluate the feedback provided from participants of the class and 2) explore the motivations and experiences of volunteer male peer facilitators trained to deliver the class. Methods: Father-focused breastfeeding antenatal (FFAB) classes were conducted in six Western Australian hospitals between August 2015 and December 2016. Following each peer facilitated FFAB class, expecting father participants completed an evaluation form to assess their satisfaction with the format, facilitation and content, in addition to whether their expectations and confidence to manage breastfeeding problems had changed. Feedback to open-ended questions was analysed using content analysis to identify learnings and suggestions for improvements. At the completion of PIFI, individual telephone interviews were undertaken with 14 peer facilitators to gain insight into their motivations for volunteering and experiences of conducting the classes. Transcripts from interviews were analysed using Braun and Clarke’s six phases for thematic analysis. Results: Participant evaluation forms were completed by 678 of the 697 father participants (98%). Overall satisfaction with class format, facilitation and content was high with 90% or more of fathers either strongly agreeing or agreeing with each positively-phrased evaluation item. Class participants enjoyed interacting with other fathers, appreciated validation of their role, were not always aware of the importance of breastfeeding or potential difficulties, valued the anticipatory guidance around what to expect in the early weeks of parenting and appreciated learning practical breastfeeding support strategies. Peer facilitators indicated they felt well prepared and supported to conduct FFAB classes. Analysis of interview transcripts revealed common experiences of the peer facilitators incorporating four themes: ‘Highlights of being a facilitator’, ‘Challenges’, ‘Mourning the project completion’ and ‘Satisfaction with training and support’. Conclusion: Father-focused breastfeeding classes supported by volunteer male peer facilitators are a feasible and acceptable way of engaging fathers as breastfeeding supporters. Trial registration: ACTRN12614000605695. Registered 6 June 2014.